2013
DOI: 10.1371/journal.pone.0067700
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Neonates Possess a CD56-Negative NK Cell Population with Reduced Anti-Viral Activity

Abstract: BackgroundNeonatal Natural Killer (NK) cells show functional impairment and expansion of a CD56 negative population of uncertain significance.MethodsNK cells were isolated from cord blood and from adult donors. NK subpopulations were identified as positive or negative for the expression of CD56 and characterized for expression of granzyme B and surface markers by multi-parameter flow cytometry. Cell function was assessed by viral suppression and cytokine production using autologous lymphocytes infected with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
(79 reference statements)
7
20
1
Order By: Relevance
“…We also observed a modest correlation between the suppressive capacity of bulk NK cells and the percentage of acutely activated CD69 + CD16 − CD56 + NK cells from all infants in our cohort. This finding again suggests that activation of these cytokine-producing NK cells may be an important component for suppressing viral replication in this assay, in agreement with previous studies [12,38]. Further studies are warranted to examine the direct role of NK cell derived cytokines in HIV-1 transmission.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed a modest correlation between the suppressive capacity of bulk NK cells and the percentage of acutely activated CD69 + CD16 − CD56 + NK cells from all infants in our cohort. This finding again suggests that activation of these cytokine-producing NK cells may be an important component for suppressing viral replication in this assay, in agreement with previous studies [12,38]. Further studies are warranted to examine the direct role of NK cell derived cytokines in HIV-1 transmission.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, cases trended towards underrepresentation of CD16 + CD56 − NK cells (4.1 and 14.1%; P = 0.07) compared with controls, and these findings were also found in the refined gating strategy analysis (supplemental digital content 2, http://links.lww.com/QAD/A505). This population has been previously described as immature [12,13,31,32], suggesting a potential protective effect of having a larger pool of NK cells able to undergo differentiation into mature NK cells associated with effector functions.…”
Section: Resultsmentioning
confidence: 95%
“…With respect to their donor‐independent and subset‐specific inventory, CD56 neg NK cells were found to be well equipped for performing cellular cytotoxicity. While expression of GrzB was previously reported for the CD56 neg population , we here characterised expression patterns of all five granzymes. Interestingly, GrzH and M were detected with the highest abundance in CD56 neg as compared to CD56 dim and CD56 bright NK cells.…”
Section: Discussionmentioning
confidence: 81%
“…Studies of human infants showed that neonates had significantly lower NK cell lytic activity and the activity was further reduced by infection or sepsis (Georgeson et al, 2001;Uksila et al, 1982). NK cells of infants also had reduced antiviral activity such as defective killing of virus infected cells and reduced cytokine secretion (Jacobson et al, 2013). Collectively, reduced NK cell activity and NK cell frequencies may have contributed to the early onset of virus shedding and the severe clinical signs in the suckling versus weaned pigs.…”
Section: Discussionmentioning
confidence: 99%